The Combined Effect of Jet and Atmospheric Turbulence on the Propagation of Airborne Partially Coherent Array Beams. Issue 6 (8th April 2022) - Zhang, Yu‐Qiu; Deng, Yu; Hou, Tian‐Yue; Ma, Peng‐Fei; Su, Rong‐Tao; Zhou, Pu
Abstract: The exhaust from engines close to the fuselage can cause extreme turbulence and have a significant impact on the performance of airborne laser systems. In this paper, the combined effect of the jet engine and atmospheric turbulence on propagation of a Gaussian Schell‐model (GSM) array beam over long distances is studied in detail. Based on the two‐step propagation method, the analytical expressions of the cross‐spectral density (CSD) function, mean‐squared beam width and spectral degree of spatial coherence (DOC) of GSM array beams are derived. It is shown that the jet engine turbulence has a significant effect on the beam broadening even at a very short distance. As the propagation distance in the jet engine turbulence increases, the beam width is less effected by the spatial coherence. Meanwhile, the resistance of lower spatially coherent beam to the turbulence increases as the distance of the jet engine turbulence or the strength of the atmospheric turbulence increases. It is demonstrated that the effect of jet engine turbulence on the beam spreading can be equivalent to moderate or even severe atmospheric turbulence. Moreover, the DOC is a function with oscillatory phenomenon when the propagation distance is short or the strength of turbulence is low. Abstract : The combined effect of the jet engine and atmospheric turbulence on propagation of an airborne Gaussian Schell‐model (GSM) array beam is studied. The results show that the jet engine turbulence has a significant effect on the beam broadening. The effects of propagation distance, spatial coherence, and the equivalent atmospheric turbulent strength on the propagation properties are investigated in detail.